Development of Fish ham from Red meat of Tuna (Euthynnus affinis) - S., Siddappaji; R.M., Prabhu (Fishery Technology, 2025)
A method was developed for the preparation of "fish ham" from the red meat of tuna (Euthynnus affinis). Preparation of fish ham involves two steps. In the first step, meat of croaker (Jhonius sp.) and pink perch (Nemipterus japonicus) was separated, mixed and' ground into a paste with required additives. In the second step, red meat of tuna was filleted, cut into cubes and its colour was fixed by curing in 0.01% sodium nitrite, 0.05% ascorbic acid, 0.01% sodium tripolyphosphate, 2% salt and 1.5% sugar mixture and stored in anaerobic condition at 20C for 48 h. Finally, fish paste and cured red meat cubes of tuna were mixed in the ratio of 60:40 and packed into krehalon casing, sealed and inserted into the metallic box type retainers and heat processed at 88-90Â°C for 105 min and cooled at 10oC for 20 min. Acceptability of fish ham was studied by chemical, microbiological and organoleptic tests. The product had excellent appearance, taste and texture. At ambient conditions the product had a shelf life of 6 days and at refrigerated condition 42 days.